2012
DOI: 10.1016/j.peptides.2012.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) abrogates mitogen-stimulated proliferation of cardiac fibroblasts

Abstract: Previous studies showed that angiotensin-(1-7) [Ang-(1-7)] attenuates cardiac remodeling by reducing both interstitial and perivascular fibrosis. Although a high affinity binding site for Ang-(1-7) was identified on cardiac fibroblasts, the molecular mechanisms activated by the heptapeptide hormone were not identified. We isolated cardiac fibroblasts from neonatal rat hearts to investigate signaling pathways activated by Ang-(1-7) that participate in fibroblast proliferation. Ang-(1-7) reduced 3H-thymidine, -l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 61 publications
1
41
1
Order By: Relevance
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 87%
“…Several studies exist, revealing a cardioprotective role of ACE2 and Ang(1-7) (Ferreira et al, 2001;Pei et al, 2010;Johnson et al, 2011;Dong et al, 2012;Feng et al, 2012;McCollum et al, 2012). In contrast to the above mentioned proarrhythmic effect of high Ang(1-7) concentrations, Ferreira et al detected reduced cardiac arrhythmias induced by ischemia/reperfusion associated with low dose Ang(1-7) if acutely administered (Ferreira et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ang-(1-7) was generally thought to inhibit the proliferation of some cell types, including tumor cells, vascular smooth muscle cells and cultured neonatal cardiac myocytes (16,17); but in some other cell types, such as fibroblasts, epidermal stem cells, keratinocytes and hematopoietic progenitors, Ang-(1-7) stimulates cell proliferation (18,19). Thus, whether Ang- (1-7) is an antiproliferative or proproliferative agent for particular tumors or host cells may be an important consideration for understanding the role of RAS in the carcinogenic process and the application of RAS blockade in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies in both adult and neonatal rat cardiac fibroblasts have demonstrated that Ang-(1-7) inhibits proliferation and collagen production [57,58]. In neonatal rat cardiac fibroblasts, Ang-(1-7) achieved this via reduced AngII-mediated phospho-ERK1 (extracellular-signal-regulated kinase 1) and -ERK2 levels and increasing DUSP1 (dual-specificity phosphatase 1) activity, which in turn reduced MAPK (mitogenactivated protein kinase) activity and prevented production of proproliferative prostaglandin-2 [58].…”
Section: Effects Of Ang-(1-7)mentioning
confidence: 99%